Educar para a sabedoria do amor: a epifania do rosto do outro como uma pedagogia do êxodo - Rosa, Luís Carlos Dalla (2010)
Starting from a theological perspective, this dissertation explores the concept of alterity or otherness, as developed by Emmanuel Lévinas, a French-Lithuanian Jewish philosopher, outlining consequences for both an educative liberating reflection and praxis. It is an encounter with the Ethics of Alterity as expressed by the love of wisdom of the Greeks, but which has its meaning fertilized and nourished by the wisdom of love of the prophets. The contribution this study intends to offer, possibly revealing something original, may be thus announced: alterity states a pertinent wisdom aiming at the fruition of an ethical education, in which the subject is called to an exodus, a coming out of oneself toward another. Hence the sense of an education to the wisdom of love that covers the meaning of one‟s own freedom. This research paid attention to the Word that resounds the clamor of the other who asks for hospitality. Totality and Infinite, one of the masterpieces of the above named author, although not exclusively, shall be the reference to the study which assumes hermeneutic phenomenology as both its descriptive and interpretative path. However, it goes without saying that the ethical levinasian priority overflows the boundaries of what the research methodology may be. The thesis is made up of six chapters. The first deals with the concept of alterity the way it is described in its correlation with the face of the other. In Lévinas‟ writings, there is a kind of twisting, a trauma, in which the reason of maieutics, of cogito, of ontology, of totality, of the primacy of the ego are deeply questioned by the face that makes itself proximity and announces the logos of the Infinite, ethics, fertility, hospitality. Thus we can perceive the meaning of the exodus that has its development scrutinized within the second chapter. Over and above the power of violence, war, exclusion, in short, of barbarism that denies the other, Ethics sets forth the unheard of interpellation: I have witnessed the affliction of my people (Ex 3.7). In the third chapter, alterity is confronted with the western historical-cultural perspective, emphasizing the permanent interdiction of the other, especially as relating to the face of the foreigner, the woman, the child, the young. Then, it is with the face of the young that the fourth chapter deals, in this section being up to the current capitalist culture of consumption, where there exists an appalling discarding of the human. Within this context, starting in the fifth chapter, education is introduced as a possibility to incite the ethical sensibility within the life dynamics of the human being. To meet the other is to meet a master who questions my condition as subject, making an ethical teaching possible. Finally, the last chapter, besides promoting the idea of an exodus pedagogy, presents an encounter of the levinasian ethics with Paulo Freire‟s pedagogy. The Ethics of alterity meets in Freire with an education that develops in the horizon of welcoming, hospitality, non-indifference, in short, of subjectivity leavened by the norms of alterity.